A performance analysis of a new secondary standard dosimetry laboratory irradiation system. (November 2021) - Amit, Gal; Hershkovitz, David; Levi, Yaniv; Hershko, Itzik; Datz, Hanan
Highlights: Ionizing radiation measurement. Ionizing radiation facility calibration. Measurement analysis. Uncertainty calculation. Abstract: This study reviews the performance analysis of a commercial 137 Cs irradiation system that has recently been installed in the Secondary Standard Dosimetry Laboratory (SSDL) at the Soreq Nuclear Research Center (SNRC). The SSDL is responsible for calibrating calibration facilities and for calibrating most protection level radiation monitoring instruments used in medical, nuclear, industrial and academic settings in Israel. Until recently, these monitoring instruments have been calibrated by a 40-year-old irradiation system. At the end of 2018, a new Hopewell Designs Inc. ® irradiation system was installed at our SSDL. This system employs the most advanced radiation safety standards, along with 21st century source automation methods. In this work, we review the system's performance. Our analysis shows excellent results in terms of repeatability, robustness, linearity, and beam uniformity. Additionally, the system accuracy was tested by participating in an international IAEA postal audit, and here too, excellent results were obtained.